2013
DOI: 10.1038/sc.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

Catheter length preference in wheelchair-using men who perform routine clean intermittent catheterization

Abstract: Study design: Prospective, unblinded, multicenter, randomized, controlled, cross-over study assessing user preference and ease of use characteristics of two gel intermittent catheters in 81 self-catheterizing wheelchair-using men. Objectives: To evaluate the male user's preference between a 30-cm and a 40-cm intermittent catheter (Apogee Intermittent Catheter, Hollister Incorporated, Libertyville, IL, USA) regarding the ease of insertion and removal, ability to control the catheter during insertion, bladder em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinu 2012 (NRS) (38) Vapnek 2003 (RCT) (24) De Ridder 2005 (RCT) (25) Pachler 1999 (RCT) (17) Cardenas and Hoffman 2009 (RCT) (36) Bennett 1997 (RCT) (16) Cardenas 2011 (RCT) (30) Fingerhut 1997 (RCT) (14) Charbonneau-Smith 1993 (NRS) (39) Moore 2006 (RCT) (26) Quigley PA 1993 (RCT) (12) Duffy LM 1995 (RCT) (13) Sùrensen 1999 (RCT) (18) Mauroy 2001 (RCT) (20) BIERING-SØRENSEN 2007 (RCT) (29) Costa 2013 (RCT) (33) Chartier-Kastler 2013 (RCT) (34) Chartier-Kastler 2011 (RCT) (31) Domurath 2011 (RCT) (32) Johansen 2007(NRS) (40) Johansson 2013 (RCT) (35) Denys 2012 (NRS) (41) Diokno 1995 (NRS) (42) Fader 2001 (RCT) (21) Pascoe 2001 (RCT) (22) Witjes 2009 (RCT) (37) Wyndaele 2000 (RCT) (19) Ginnantoni 2001 (RCT) (23) Waller 1997 (RCT) (15) PEARMAN 1991(RCT) (11) Sekiguchi et al 2007 (RCT) (28) 0% 20% 40% 60% 80% 100%…”
Section: Other Biasmentioning
confidence: 99%
“…Five RCTs compared compact hydrophilic with standard hydrophilic catheters in terms of satisfaction and/or quality of life (Table 3a). 29,[31][32][33][34] Only one article demonstrated a significant increase in satisfaction reported from patients using a compact hydrophilic catheter, when compared with patients using a standard hydrophilic catheter. 34 Chartier-Kastler et al, 34 conducted a prospective randomized crossover study to compare compact with standard catheters in terms of quality of life.…”
Section: Patient's Satisfaction and Quality Of Lifementioning
confidence: 99%
“…Five two-arm cross-over trials compared a shorter length hydrophilic catheter with a standard hydrophilic catheter. 12,15,17,39,40 One trial 40 compared 40 cm vs. 30 cm catheter length in a pre-lubricated system with integrated collection bag. Subjects in this trial all preferred the longer length catheter.…”
Section: Outcome 3: Participant Reported Outcomesmentioning
confidence: 99%
“…Almost all the men preferred the longer 40-cm catheter, and significantly more reported that it was better than the shorter (30 cm) catheter in terms of handling during insertion, insertion into the urethra, directing urine into a receptacle, fully draining the bladder, and removing from the urethra. 12 Bolinger and Engberg 13 surveyed men and women in the United States performing ISC for 2 or more months (mean = 60 months) about barriers to self-catheterization. Most reported at least 1 barrier to ISC: lack of access to bathrooms, lack of dexterity, and cost of supplies the most frequently reported barriers.…”
Section: Issues For Consideration When Developing Educational Interve...mentioning
confidence: 99%